The relationship between employee commitment to strategy implementation and employee satisfaction - Chijioke Esogwa Nwachukwu; Helena Chladkova; Fadeyi Olatunji (Trends Economics and Management, 2018)
Purpose of the article: The mobile telecommunication sector in Nigeria has attracted highest foreign direct investment, consistently created jobs more than any sector in the economy. Encouraging employees commitment to strategy implementation can have a positive impact on employee satisfaction level. Methodology/methods: This study used a descriptive quantitative research approach. The survey method was used to collect data from four mobile telecommunication firms in Nigeria. We administered 120 questionnaires to employees of the sample firms, 105 questionnaires were returned and analysed using the regression analysis, Pearson correlation and ANOVA techniques. Scientific aim: This study examines the relationship between employee commitment to strategy implementation and employee satisfaction in mobile telecommunication firms in Nigeria. Findings: The results show that employee commitment to strategy implementation has a positive and significant relationship with employee satisfaction. Employee commitment to strategy implementation is correlated with employee satisfaction, the more committed employees are to their firms strategy implementation, the higher their level of satisfaction with their firms. Thus, employee commitment to strategy implementation have positive impact on employee satisfaction. Our formulated hypothesis is supported. Conclusions: This study provides a better understanding on the importance of employee commitment to strategy implementation in improving the level of employee satisfaction. This study suggests that employee commitment to strategy implementation is an important factor of employee satisfaction. Thus, policymakers, business executives, and HR managers must create an organisational culture and climate that support employee commitment to strategy implementation to improve employee satisfaction. The authors recommended that firms should elicit the commitment of their employees at the strategy implementation stage as this will boost their level of satisfaction. A satisfied employee will be more productive and this will in turn improve the firm's performance.
Keywords: L20; M10; 650; Strategy implementation; employee commitment; resource-based view; employee satisfaction